The Impact of Tourism Products and Sign Systems on Visitor Satisfaction in the Polowijen Cultural Village (International Conference of Graduate School on Sustainability (ICGSS), 2021)
Polowijen Cultural Village is one of the thematic villages in the Blimbing area of ​​Malang City. This village is designed by cultural heritage which makes it the main attraction for the Polowijen Cultural Village. Visitor satisfaction is one of the factors that play an important role in the development of the Polowijen Cultural Village. The purpose of this study was to determine the effect of attractions and sign systems on visitor satisfaction. This study used 96 respondents who had visited the Polowijen Cultural Village. The method used in this study is a quantitative method with a descriptive approach. Data collection techniques by distributing questionnaires with a Likert Scale. The results of this study are: (1) attraction has a positive and significant effect on visitor satisfaction; (2) sign system has a positive but not significant effect on visitor satisfaction; (3) attractions and sign systems have a positive and significant effect on visitor satisfaction. Keywords: Attractiveness, Sign System, Visitor Satisfaction.